LaserIMD kernel for 'The effect of the zero-field splitting in light-induced pulsed dipolar electron paramagnetic resonance (EPR) spectroscopy' - Scherer, Andreas; Yildirim, Berk; Drescher, Malte (My University, 2023)
This repository contains the software for the calculation of the LaserIMD kernel for the manuscript 'The effect of the zero-field splitting interaction in light-induced pulsed dipolar electron paramagnetic resonance (EPR) spectroscopy' submitted for pubilcation at Magnetic Resonance. The code is also available at github (https://github.com/andreas-scherer/LaserIMD_kernel).
Keywords: 540